Analysis of Energy Consumption and Electrical Power Efficiency on Conventional and CNC Lathes at CV Wakinara Teknik - Rifky Maulana; Rahmaniar Rahmaniar; Parlin Siagian (Jurnal Info Sains : Informatika dan Sains, 2026)
This research is motivated by the high consumption of electrical energy in the machining process that has not been balanced with an analysis of power usage efficiency, especially on conventional lathes and CNC machines at CV Wakinara Teknik. The lack of monitoring and evaluation of energy consumption leads to potential electricity waste and suboptimal machine utilization in production activities. Therefore, this study aims to analyze the energy consumption and level of electrical power efficiency on both types of machines to determine the comparison of energy performance and potential savings opportunities. The research method used includes direct measurement of electrical parameters such as voltage, current, power, and power factor during the machine operation process. The data obtained are then analyzed to calculate energy consumption and power usage efficiency on each machine. In addition, a comparison of energy consumption characteristics between conventional and CNC lathes is conducted under similar workload conditions. The results show that CNC machines tend to have more stable energy consumption and higher power efficiency than conventional lathes, although under certain conditions their power consumption is greater due to the use of an automatic control system. Meanwhile, conventional lathes have higher fluctuations in energy consumption and relatively lower efficiency. These findings indicate that the application of CNC machines can improve energy efficiency in production processes, as well as provide a basis for developing more optimal energy management strategies in industrial environments.